Water supply of cities - Pfuetze, Carl Frederic (My University, 1893)
Introduction: The problem of getting water for domestic use has been a question from the earliest times. The first source was probably a spring or creek and no great system was needed. Each person used his own reservoir to carry it. But when the population centers in large numbers, as in cities, the friction experienced in obtaining wholesome water is very great and some provision must be made. Among the first systems of supplying water to a large community was that in Jerusalem. This task was undertaken by Soloman. It was the supplying of Jerusalem with water taken from Bethlehem, conducted in stone conduits three foot square and fifteen inches thick.
Citation: Pfuetze, Carl Frederic. Water supply of cities. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Water; Domestic use; Reservoir; Solomon and Jerusalem; Theses; Manuscripts (documents)